Cobalt-, zinc- and iron-bound forms of adenylate kinase (AK) from the sulfate-reducing bacterium Desulfovibrio gigas: purification, crystallization and preliminary X-ray diffraction analysis - Kladova, A. V. (2012)
Acta Crystallogr Sect F Struct Biol Cryst Commun. 2009 Sep 1;65(Pt 9):926-9